The counter-revolution of science : - Hayek, Friedrich A. von (Free Press, 1952)
Early in the last century the successes of science led a group of French thinkers to apply the principles of science to the study of society. These thinkers purported to have discovered the supposed 'laws' of society and concluded that an elite of social scientists should assume direct control of social life. The Counter-Revolution of Science is Nobel Laureate Friedrich Hayek's forceful attack on this abuse of reason.